(untitled) (Bangladesh Journal of Pharmacology, 2019)
The anti-diabetic effect of Atractylis gummifera (plant used in traditional Moroccan medicine) has been evaluated in type 2 diabetic mice model. The mice were divided into five groups: Normal control, diabetic control, diabetic treated with aqueous macerate (500 mg/kg), diabetic treated with methanol macerate (500 mg/kg) and diabetic treated with metformin (300 mg/kg). The treatment of the mice was performed by daily gastric gavage for 5 weeks. The monitoring of the mice was carried out weekly by fasting glucose and measurement of biochemical parameters at the end of treatment. The aqueous macerate of A. gummifera was most effective that reduced the fasting blood glucose with 62.7%. In addition, this extract restored the biochemical parameters of diabetic mice to normal. Video Clip of Methodolpogy: 5 min 53 sec: Click to watch